A bi-objective approach to minimise cost and CO2 emissions in intermodal freight transport for biomass energy. (8th November 2022) - Shoukat, Rizwan; Zhang, Xiaoqiang
The purpose of this study is to investigate the bi-objective problem of minimising cost and CO2 emissions in the supply of biofuels for producing cheaper biomass energy in Pakistan. Our research studied the problem by taking wheat straw (WS) and Brassica campestris (BC) as biofuels for a biomass plant. The bi-objective problem has been formulated with a mixed-integer linear programming (MILP) model. The data is obtained from one of the largest paper and board (P&B) industries in Pakistan. We solved our problem by applying a genetic algorithm (GA). Our results show a 50.4% saving by switching from road to road-rail transport to meet the demand of 1, 000 tons of biofuels per day, as well as a 66.35% reduction in CO2 emissions. Pareto optimal solutions generated by the genetic algorithm facilitate decision makers by trading off cost and CO2 emissions. Moreover, this study can be extended by investigating the effects of biomass energy on the price of the product and markets.